São Tomé and Príncipe - Beyond Connections : Energy Access Diagnostic Report Based on the Multi-Tier Framework - Brutinel, Marina; Wang, Yuhan; Koo, Bryan Bonsuk; Portale, Elisa; Rysankova, Dana (World Bank, Washington, DC, 2019)
São Tomé and Príncipe (STP) is one of the smallest economies in Africa, a lower-middle-income, developing small-island state with a fragile economy, and it is therefore highly vulnerable to exogenous shocks. The World Bank, with support from the energy sector management assistance program (ESMAP), has launched the global survey on energy access, using the multi-tier framework (MTF) approach. The survey’s objective is to provide more nuanced data on energy access, including access to electricity and cooking solutions. The MTF approach goes beyond the traditional binary measurement of energy access to capture the multidimensional nature of energy access and the vast range of technologies and sources that can provide energy access, while accounting for the wide differences in user experience. The importance and wide-ranging impact of energy access is recognized by the United Nations under sustainable development goal 7.1, which seeks universal access to affordable, reliable, and modern energy services. The government of STP has been committed to achieving sustainable development goal 7 to benefit its people, and has thus collaborated with the World Bank to realize the MTF survey to obtain guidance on setting targets, policies, and investment strategies for enhancing energy access.